2015
DOI: 10.5432/ijshs.201519
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Changes in Bat Grip Position on Baseball Bat Swing Timing, Ground Reaction Force, and Muscle Activation Characteristics*

Abstract: This study aimed to clarify the eŠects of changing to a short bat grip position from the long bat grip position on baseball bat swing timing, peak ground reaction force with the front leg, and activation of the upper and lower limb muscles.Nine male college baseball players participated in this study. By using a batting simulator, the coincident timing task was to swing the bat coincidentally with the arrival timing of a moving target by using the long or short bat grip position. The batter performed 10 sets o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The swing time was defined as the time to peak ground reaction force to impact [19,24]. Results of this study showed the average percent activation of the stride leg during swing time of the VL close to 80% of MVIC, 40% of the BF, 80% of the MG, and 60% for the TA of their swing trials [18].The percent activation during the swing phase in our study was 160.321.9% for the H, 164.363.6% for MG, 20.393.6% for the VMO, and 20.334.1% for the TA. We chose to examine changes in electrical activity of both the vastus medialis and semitendinosus for their role in extending and flexing the knee respectively.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…The swing time was defined as the time to peak ground reaction force to impact [19,24]. Results of this study showed the average percent activation of the stride leg during swing time of the VL close to 80% of MVIC, 40% of the BF, 80% of the MG, and 60% for the TA of their swing trials [18].The percent activation during the swing phase in our study was 160.321.9% for the H, 164.363.6% for MG, 20.393.6% for the VMO, and 20.334.1% for the TA. We chose to examine changes in electrical activity of both the vastus medialis and semitendinosus for their role in extending and flexing the knee respectively.…”
Section: Discussionmentioning
confidence: 85%
“…A study completed Ohta and Nakamoto 2015 [17] does not align with the results of our study. Investigators of this study wanted to examine differences in ground reaction forces and muscle activation characteristics of the stride leg vastus lateralis (VL), BF, and MG based on different bat grips in nine collegiate baseball players [18].Each participant swung a bat at a moving target to simulate a ball being thrown towards home plate. The swing time was defined as the time to peak ground reaction force to impact [19,24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations